The sound and visual dramaturgy of Romeo Castellucci - Fanelli, Carlo (Mimesis Journal, 2024)
Known for a theater whose essence is built on the totality of the arts, Romeo Castellucci has, over time, confirmed his position of radical subversion of the relationship between dramaturgy and literature. Some of his performances will be analyzed as an example of this position, in order to observe how a “writing” advances in them which is made up of images, sounds and visual architectures and how the word, understood dramaturgically, is subjected to a mercurial regime of and surfacing, of technological redefinition in its being an act delivered on stage or written according to an unprecedented compositional process. From an imaginative language, stripped down, reduced to five words of the Generalissima, to the rhetoric of the voice and its carnality that composes a journey into the reversed image of the actor on stage (Giulio Cesare). Rethinking tragedy in contemporary terms, abandoning the concepts of guilt and destiny and a representation based on myth, redefining the tragic in the living as a dramatic, sound and vocal composition (Tragedia Endogonidia). The explantation of Hawthorne’s narrative text in The Shepherd’s Black Veil replaced by the drama of the image and its “presentation” to a watching community. The diachrony supported by the statuesque scenic gestures of Hölderling’s Empedocles that flows into the triumph of the sound image that manifests its dramaturgical power (The Four Seasons Restaurant). Aphasia and glossolalia that define the creation of another language that emanates from a choreographic and community code emerging from a remote era (Democracy in America). Finally, a «discipline of Western representation» from which originates a liturgy of the word that nourishes a tragedy in which bodies and machines have their anabasis in an extra-diegetic space (La Vita Nuova).